MENINGKATKAN KOMPETENSI GURU DALAM MELAKUKAN PROSES PEMBELAJARAN MELALUI METODE KUNJUNGAN KELAS : PENELITIAN TINDAKAN DISEKOLAH BINAAN - Aan Andriyani (Universitas Nasional, 2018)
Improving Teacher’s Competence on Learning Process Through Class Visit Method Doing action research on supervising the guided teachers of Junior High School in Bekasi. Sixteen subject teachers become a target of the research.This research started from July until November 2016. Class visit Method did by the supervisor to find the teacher’s problem in the school target.It is done for coaching the teacher’s target intensely.At first,the researcher interviewedsome teacher’s and found that they were less active on provide the teaching learning process.They were lack of preparation such as preparing the lesson planning and still using the conventional method. The data found the active teacher on teaching learning process is 6,25 %.After coaching by the supervisor, in cycle I, the data has improved into 66,67 % and 93,75 % in cycle II.There was also improvement on preparing the lesson planning.The data found 2,13 at first.After coaching by the supervisor in cycle I , it improved into 3,34 and 3,62 in cycle II.It means that there was changing on teacher’s learning process after coaching and class visit method going held.